Upah dan Kepuasan Kerja - Insan, A. Nur (JURNAL ADMINISTRASI BISNIS (JAB), 2020)
The purpose of this research was to find the employee’s salary and job satisfaction. This research is descriptive qualitative. Eight informants are employees. Data collection techniques in-depth interviews and observation. The results of found eight informants satisfied with their work, satisfied with the supervisor, satisfied with a coworker but not satisfied with salary because they were still below the Provincial minimum wage standard. Five informants were dissatisfied with shopping voucher gifts as employee salaries. Their informants were satisfied with promotion because it was promoted and five informants did not get the promotion.